Śataka catuṣṭaya saṅgraha : Nīti, Srṅgāra, Vairāgya, Vijñāna, ane prastāvika, mūḷa śloka, bhāṣāntara, ane samajuti sameta - Bhartrhari (Gujarātī Presanā Mālīka, 1906)
Classical didactic verses with Gujarati translation; contains Vijñāna śataka for the first time along with Nīti, Srṅgāra, and Vairāgya śataka which are published under title, Śatakatraya.